Institute of Animal Health and Veterinary Biologicals, Hebbal, Bangalore 560024, Karnataka - K, Sripak; Kowali, Shrikant; P, Giridhar; SM, Byregowda (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was undertaken to assess the prevalence of bovine tuberculosis among buffaloes in Belgaum, Dharwad and Bagalkote districts of North Karnataka, for a period of eight years (2002 to 2009). A total of 2184 buffaloes belonging to 30 organized farms were screened by single intradermal tuberculin test using bovine tuberculin Purified protein derivative. Overall prevalence of tuberculosis among buffaloes was found to be 0.96 per cent. Prevalence was higher in females (0.97%) than males (0.84%) and in Murrah (1.02 %) than Surthi (0.85 %). Analysis of the temporal pattern revealed a gradual declining trend over a period of eight years. animals also occurs. (OIE Manual, 2016). Delayed Bovine tuberculosis is a chronic bacterial disease of cattle, other domesticated animals and certain wildlife populations caused by Mycobacterium bovisa member of Mycobacterium tuberculosis complex. The disease has socio economic, public health and economic importance. Cattle is considered as true host of M. Bovis. Disease has also been reported in buffaloes (De-Lisle et al., 2001). Tuberculosis causes heavy economic losses due to poor carcass quality, low quality hide and reduced milk yield (Ghuman et al., 2013). Aerosol exposure to M. Bovisis considered as the most frequent route of infection, but infection by ingestion of contaminated material, contact with infected hypersensitivity test as detected by tuberculin test is the standard method for detection of bovine tuberculosis (OIE Manual, 2016).The prevalence of bovine tuberculosis varies from region to region and even from one farm to other (Javed et al., 2006). Review of literature reveals paucity of data about the prevalence of bovine tuberculosis in animal population in North Karnataka. Hence the present study was undertaken to assess the overall prevalence of bovine tuberculosis among buffaloes of North Karnatka and also to assess the prevalence in respect to year, sex and breed in the study area.